Reciprocal regulation of actomyosin organization and contractility in nonmuscle cells by tropomyosins and alpha-actinins - Hu, Shiqiong; Grobe, Hanna; Guo, Zhenhuan; Wang, Yu Hsiu; Doss, Bryant L.; Pan, Meng; Ladoux, Benoît; Bershadsky, Alexander D.; Zaidel-Bar, Ronen (Molecular Biology of the Cell, 2019)
Contractile arrays of actin and myosin II filaments drive many essential processes in nonmuscle cells, including migration and adhesion. Sequential organization of actin and myosin along one dimension is followed by expansion into a two-dimensional network of parallel actomyosin fibers, in which myosin filaments are aligned to form stacks. The process of stack formation has been studied in detail. However, factors that oppose myosin stack formation have not yet been described. Here, we show that tropomyosins act as negative regulators of myosin stack formation. Knockdown of any or all tropomyosin isoforms in rat embryonic fibroblasts resulted in longer and more numerous myosin stacks and a highly ordered actomyosin organization. The molecular basis for this, we found, is the competition between tropomyosin and alpha-actinin for binding actin. Surprisingly, excessive order in the actomyosin network resulted in smaller focal adhesions, lower tension within the network, and smaller traction forces. Conversely, disordered actomyosin bundles induced by alpha-actinin knockdown led to higher than normal tension and traction forces. Thus, tropomyosin acts as a check on alpha-actinin to achieve intermediate levels of myosin stacks matching the force requirements of the cell.
CRIS-Team Scopus Importer:2024-02-19